La influencia de los medios de comunicación en la percepción de la realidad del individuo : White noise de Don DeLillo y Saturday de Ian McEwan - Ortín Calabrese, María Melina (2019)
This work aims at analysing the role of mass media in contemporary families, the influence that news have on our perception of reality and on the behaviour of the members of a contemporary society. More specifically, it intends to analyse the influence of mass media on the Gladney family's perception of reality and behaviour in White Noise (1985) by Don LeLillo, and the influence of mass media on Henry Perowne's perception of reality and behaviour in Saturday (2005) by Ian McEwan. Mass media is communication—whether written, broadcast, or spoken—that reaches a large audience. This includes television, radio, movies, the Internet, newspapers, magazines, and so forth. The Modern man is immersed in a society that depends on information and communication to keep moving and doing their daily activities. Contemporary life cannot be imagined without mass media. Members of any segment of society are constantly exposed to the media. Mass media has become a daily and essential necessity to the contemporary man. Almost every house in the civilized world features a TV set which is constantly on, playing an important role in the family, not only as a form of entertainment but also as a means of information.